2007
DOI: 10.1145/1345375.1345441
|View full text |Cite
|
Sign up to set email alerts
|

A survey of literature on the teaching of introductory programming

Abstract: Three decades of active research on the teaching of introductory programming has had limited effect on classroom practice. Although relevant research exists across several disciplines including education and cognitive science, disciplinary differences have made this material inaccessible to many computing educators. Furthermore, computer science instructors have not had access to a comprehensive survey of research in this area. This paper collects and classifies this literature, identifies important work and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0
9

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 327 publications
(94 citation statements)
references
References 95 publications
0
74
0
9
Order By: Relevance
“…Uno de los elementos clave en la introducción a la programación es el lenguaje escogido; siendo los otros elementos: el currículo, la pedagogía y las herramientas empleadas en el proceso de enseñanza+aprendizaje (Pears, et al, 2007). La selección del lenguaje de programación se ha estudiado únicamente en 22 estudios primarios que van desde los años cincuenta hasta 2012 (Stefik, et al, 2015).…”
Section: Pensamiento Computacional Y Programaciónunclassified
“…Uno de los elementos clave en la introducción a la programación es el lenguaje escogido; siendo los otros elementos: el currículo, la pedagogía y las herramientas empleadas en el proceso de enseñanza+aprendizaje (Pears, et al, 2007). La selección del lenguaje de programación se ha estudiado únicamente en 22 estudios primarios que van desde los años cincuenta hasta 2012 (Stefik, et al, 2015).…”
Section: Pensamiento Computacional Y Programaciónunclassified
“…A survey and taxonomy of languages and environments used to make programming easier to learn for novice programmers is presented in [53]. Another good survey and classification of different programming languages used in introductory programming courses is given in [54]. A very recent brief history of learning to program is given in [55].…”
Section: B Choice Of Programming Languagementioning
confidence: 99%
“…It is widely used in visual debugger of Integrated Development Environment(IDE) [2]. On the other hand, studies have shown that PV can also improve beginner's understanding of computer program [3], [4].…”
Section: Introductionmentioning
confidence: 99%